Team cohesion and communications in Surgery: Re-designing the WHO Surgical Safety Checklist (SSC) to support teamwork, patient safety and Safety 2 practices - CAHILL, JOAN; Conroy, P.; Tobin, C.; Dardis, C. (Irish Ergonomics Society, 2016)
This paper presents a case for redesigning the existing surgical safety checklist (SSC), to better support team cohesion/communications and safety culture. In so doing, it proposes the following enhancements: The redesign of the SSC needs to take into account Safety 11 concepts Redesign activities need to link to broader hospital safety management concepts and practices The SSC should be located in the context of both formal and informal planning/briefing practices involving different members of the multi- disciplinary team prior to the ‘sign in’ stage and post ‘sign-out’ Further, this paper argues that good teamwork will necessitate behaviour change on the part of all relevant actors in surgery. This behaviour change will be underpinned by wider organisational change. Critically, organisational change is necessary to address the socio-technical ‘root causes’ of non-compliance and specifically, cultural issues. In support of this, this paper draws upon the findings of the first phase of a clinical audit pertaining to teamwork practice and the use of the SSC, at a Dublin hospital. Overall, these enhancements - which go beyond existing guidelines (Health Service Executive and World Health Organisation), will better support team cohesion/communication and safety culture. This in turn will positively impact on patient safety.
Annual Irish Ergonomics Conference
Keywords: Safety; Surgical safety; Hospital safety management; Surgery; Intelligent Content & Communications; Checklist design; Safe Surgery; Teamwork